Power Electronics - Singh M. D. (New Delhi, Tata McGraw-Hill Publishing Company Limited, 2005)
Introduces updated power semiconductor devices, their basic operations and characteristics. Illustrates how these devices can be used in controlled rectifier circuits, inverter circuits, chopper circuits, cycloonverter circuits and dual converter circuits. Presents various aspects of power semiconductor devices, controller DC and AC drives, and their performance analysis. Highlights the various commercial and industrial application circuits.